Yellow bleeding heart: A widely used hypotensive and hypoglycemic medicinal plant of North-east India - Tatan, Tantulung; Mehra, T S (Indian Horticulture, 2023)
Dactylicapnos scandens (D. Don) Hutch (Syn. Dicentra scandens (D. Don) Walp.), is a perennial scandent herb that belongs to the family Fumariaceae. It has horizontal tubers with a network of fibrous roots, and yellow heart-shaped blooms. It can be found in the Central and Eastern Himalayan regions. The plants feature four petals, two of which are actinomorphic whorls that are located opposite each of the outer petals. Ovary is superior, unilocular, bicarpellate, narrowly linear to broadly ovate-oblong in form, with parietal placentation and thin style. Fruit is an indehiscent, fleshy capsule that is ovate to oblong in shape, pale yellow-white when young, and turns reddish. Corydine, isocorydine, protopin, aporphine alkaloids, glaucine and isocorydine are the chemical compounds present in the plant. Certain tribal people in North-East India have historically utilized this significant ethnomedicinal plant as a treatment for various health concerns.